Equine Tendinopathy Therapy Using Mesenchymal Stem Cells - Platonova , Svetlana; Korovina, Daria; Viktorova, Ekaterina; Savchenkova, Irina (KnE Life Sciences, 2021)
The application of animal mesenchymal stem cells has been actively studied in veterinary medicine over the past decade. In horses, the use of stem cells is mainly aimed at the treatment and maintenance of the musculoskeletal system. This review summarizes the currently published data on the therapeutic use of mesenchymal stem cells in equine tendon injuries. Tendon lesions are the most common cause of horse limp. It has been demonstrated that the use of mesenchymal stem cells compared with traditional methods of treatment can significantly reduce the re-injury. Currently, there are a large number of stem cell application protocol versions. Many researchers have obtained positive clinical results in using a combination of mesenchymal stem cells and platelet-rich blood plasma. Studies have demonstrated the safety of using allogeneic mesenchymal stem cells as an alternative to autologous. This review shows that the application of mesenchymal stem cells for horse tendon regeneration is a perspective area in veterinary medicine.